2020
DOI: 10.1186/s12961-020-00580-2
|View full text |Cite
|
Sign up to set email alerts
|

Workplace-based health research training: a qualitative study of perceived needs in a rural setting

Abstract: Background: The calls for increased numbers of researchers in rural health are growing. To meet this demand, training is needed. If training is to be effective, the value placed on research, the organisational need for research training and key targets for research skill development within a rural health organisation must be understood. Methods: This qualitative study was underpinned by a critical realist perspective that allowed exploration of the organisational, cultural and structural contexts of research t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(48 citation statements)
references
References 16 publications
0
48
0
Order By: Relevance
“…6 The diversity of health disciplines working collaboratively can develop synergy of research interests; however, finding a common multidisciplinary research interest might be difficult and take time to develop beyond individual research activity. 12 While this case study showed discipline-specific research collaborations at a local rural and university level, there was considerable cross-collaboration with a range of collaborators, particularly after 13 years (in Phase 3).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…6 The diversity of health disciplines working collaboratively can develop synergy of research interests; however, finding a common multidisciplinary research interest might be difficult and take time to develop beyond individual research activity. 12 While this case study showed discipline-specific research collaborations at a local rural and university level, there was considerable cross-collaboration with a range of collaborators, particularly after 13 years (in Phase 3).…”
Section: Discussionmentioning
confidence: 83%
“…Numerous challenges exist to the further development of rural-based research, with key barriers including a low critical mass of researchers with a common focus, 7 limited access to competitive grant funding, and a fragmentation of research activity. 12 The support and recognition from central universities to rural-based researchers have been reported as variable. 5 In addition, the nature and organisational culture of rural academic work impacts on research recognition, job security, and career progression options.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While rural and remote clinicians perceive a need to undertake research and are interested in being involved in research and research training, 7 they are often isolated and part of a small workforce with a high turnover, 8 and experience a lack of role models, access to research networks and funding opportunities 2 . Additional challenges in the rural and remote setting include the fragmentation of research activity and a lack of systems and structures to support research 9 . While health services are recognising the importance of integrating research capacity building into their organisational frameworks, initiatives tend to be site and service‐specific 1,10 and are not clearly articulated with formal educational pathways 11 …”
Section: Pathways and Trajectories Into Rural Health Researchmentioning
confidence: 99%
“…2 Additional challenges in the rural and remote setting include the fragmentation of research activity and a lack of systems and structures to support research. 9 While health services are recognising the importance of integrating research capacity building into their organisational frameworks, initiatives tend to be site and service-specific 1,10 and are not clearly articulated with formal educational pathways. 11 Concurrently, the rural and remote health research workforce also comprises an academic contingent situated within a diverse range of higher education contexts including university departments of rural health, rural clinical schools, study centres and campuses of regional universities.…”
Section: Pathways and Trajectories Into Rural Health Researchmentioning
confidence: 99%